Topics in gravitational dynamics : solar, extra-solar and galactic systems - Aussois Winter School "Open Problems of Celestial Mechanics" (2006 : Aussois, France); Benest, Daniel; Froeschle, Claude; Lega, E. (Elena) (New York : Springer, 2007)
26